PELATIHAN SAXOPHONE GUNA MEMBANTU PEMAKNAAN KATA-KATA PADA PENYANDANG BERKEBUTUHAN KHUSUS - Dominikus Catur Raharja (STT Bethel The Way, 2021)
The purpose of this study is to help people with special needs to be able to interpret words properly and correctly. Talking about children with special needs is very interesting, there are many things we can learn, we observe and we can do for them. Our attention to them is very meaningful and needed, especially for parents of children with special needs.Every development is something that parents of children with special needs look forward to, many efforts are made to stimulate their children. Not a few parents choose music as a means of stimulus. The introduction of musical instruments and regular practice is an effort and a vehicle for the development of their children. The method used is qualitative by mapping and sorting based on attention in research. Results obtained, the saxophone instrument is one of the many musical instruments that can stimulate children with special needs.Blowing and trying to sound it while practicing the saxophone can help children with special needs to be able to feel the changes in loud and soft sounds.This process can help children with special needs interpret hard and soft words. The conclusion that can be expressed is that the habit of blowing on the saxophone makes people with special needs can feel the blowing pressure with the resulting sound, which is loud and soft. Keywords: Saxophone Training, Meaning of Words, Special Needs